Validation of the Polish version of the Dizziness Handicap Inventory - Sylwia Szostek-Rogula; Ewa Zamysłowska-Szmytke (Nofer Institute of Occupational Medicine, 2019)
Background The Dizziness Handicap Inventory (DHI) was established to assess the impact of dizziness and balance problems on the quality of life. The aim of the study was to validate the Polish version of DHI for patients with vestibular disorders. Material and Methods Two hundred and thirty patients diagnosed with vestibular impairment and/or positional vertigo were included in the study. The mean age of the study group was 56.2 years (SD = 13.6). The factor structure (the principal component analysis − PCA), internal consistency (Cronbach's α), and discrimination ability (the receiver operating characteristic [ROC] curve) were examined. Results satisfactory internal consistency was found (Cronbach's α coefficient = 0.92), while no floor or ceiling effect was revealed. The Dizziness Handicap Inventory demonstrated a good ability to discriminate between patients with and without the handicap (sensitivity and specificity about 80%, the cutoff point = 56). In PCA a 3-factor solution was obtained, with the factors related to restrictions in daily life, positional symptoms and visual-vestibular symptoms, which was not in agreement with the subscales provided in the original version. Conclusions The Polish version of DHI demonstrates satisfactory measurement properties and can be used to assess the impact of dizziness on handicap and the quality of life. The functional, emotional, and physical subscales were not confirmed. In particular, the functional subscale revealed no satisfactory internal consistency which provides an indication for further studies. Med Pr. 2019;70(5):529-34